AUTOGENERATOR PARAMETRIC SENSORS OF THE MAGNETIC FIELD WITH A HALL ELEMENT AND ATWO-COLLECTOR BIPOLAR MAGNETOTRANSISTOR - OSADCHUK, JAROSLAV; OSADCHUK, ALEXANDER; OSADCHUK, VLADIMIR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Self-oscillating parametric magnetic field sensors with a frequency output signal based on transistor structures with negative differential resistance with primary magnetically sensitive Hall elements and a bipolar two-collector magnetically sensitive transistor are proposed, moreover, the primary magnetically sensitive elements also act as active circuit elements. Magnetic field sensors with a frequency output do not require analog-to-digital converters and amplifying devices for further processing of information signals, which reduces the cost of information-measuring equipment, in addition, it is possible to transmit information over a distance when the sensors operate at microwave frequencies. Based on the analysis of physical processes in primary magnetically sensitive elements and self-oscillators, mathematical models of sensors were developed, on the basis of which parametric dependences of the conversion and sensitivity functions were obtained. The obtained functions clearly show the influence of each element of the primary magnetic converters and self-oscillator elements on the output frequency of the sensors in comparison with the calculations of the conversion functions from equivalent device circuits based on the Kirchhoff solution equations. It is shown that the main contribution to the conversion functions is made by a change in the magnetic induction, which causes a change in the negative differential resistance and the equivalent capacitance of the oscillatory circuit of the self-oscillator, which in turn changes the output frequency of the magnetic field sensors. Self-oscillating parametric magnetic field sensors with a frequency output signal can significantly improve the accuracy and sensitivity of measuring magnetic induction, abandon analog-to-digital converters and amplifying devices in the further processing of information signals, they also allow transmitting initial information over a distance when operating at microwave frequencies. The sensitivity of the magnetic field sensors varies from 1.45 kHz/mT to 11.95 kHz/mT when the magnetic induction changes from 0.1 to 120 mT.